Review Paper on Solar Still with Bitumenasa Phase Change Material for Water Distillation - Ganesh E. Kondhalkar, Dhanashree S. Ware, Mahesh P. Kumbhare, Vikas K. Mehtre (Mathematical Statistician and Engineering Applications, 2022)
Water is basic necessity of man. Fresh water sources are considered to be rivers, lakes and underground water reservoirs. Although, more than two-third of the earth is covered with water and remaining of the earth is land. However, the use of water from such sources is always not good, because of the polluted environment. In present work phase change material(Bitumen) is used to store the solar thermal energy in the form of latent heat, which can offer high storage capacity per unit volume and per unit mass and we can get heat in the night time for desalination. The efficiency of the solar still without PCM is about 25.19% and in presence of PCM (Bitumen) will rises.